Implementation of the Pancasila Student Profile Strengthening Project in Instilling Independent Character - Septiyani Septiyani; Suyatno Suyatno; Achadi Budi Santosa (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
Character education can be implemented in the project of strengthening the Pancasila student profile (P5). This research uses a type of qualitative research using descriptive data analysis techniques. The purpose of this study was to describe and analyze the learning project of strengthening the profile of Pancasila students (P5) in instilling independent character. The subjects of this study were the principal and fourth-grade teacher of SDN 4 Sungai Lilin, Musi Banyuasin Regency. The data collection method used by researchers involves interviews and observations from various research subjects related to data relevant to this research. Then the collected data was analyzed to obtain the validity of the research data using data triangulation. The results of this study, with the existence of P5 will make it easier for students to instill independent characters that contain Pancasila values to become better people. Through this P5 activity, students have shown good things with the value of Pancasila, so that students can recognize themselves well and improve their quality. Implementing P5 is a good strategy to instill independent character in students, with a fairly mature design and implementation. P5 can help learners to become independent individuals through the Pancasila learner profile.